Investigating the Deviation Angle Method for Ensuring Deflection at One-Lane Rural Roundabouts - Nicola Berloco; Pasquale Colonna; Paolo Intini; Vittorio Ranieri (The Baltic Journal of Road and Bridge Engineering)
Roundabouts developed as a road intersection design option has resulted in a series of nonuniform design guidance criteria in Europe, as well as in the United States and other Countries. In addition to different design specifications about the geometry of the elements constituting a roundabout (width and lanes of the circulatory roadway, entry and exit legs, splitter island), the methods for guaranteeing that vehicle paths deflect through the roundabout are also different. These methods ensure proper travel speeds between conflicting traffic flows. Currently, the main parameters used by standards to control the deflection are the deflection radius, the entry path radius, and the deviation angle. After a comparison between International deflection methods for roundabouts, this study checks the geometric requirements of the deviation angle for more than 7.000 hypothetical one-lane rural roundabouts. The Computer-Aided Design (CAD) drawing of the roundabouts takes into account the range of variability of their main geometric parameters, according to the Italian Standard. Subsequently, a number of the considered roundabouts checked with both the entry path radius and the German methods. Some results showing the greater effectiveness of the less popular deviation angle method are discussed. The main aims of this paper are: 1) to promote the deviation angle method, which is only used in Switzerland and Italy; 2) to improve standards, as regards the applicability and validity of the deflection angle method; 3) to help practitioners to know in advance the outcome of the deflection checks at the beginning of the iterative design process, once the boundary conditions are known.